2001
DOI: 10.1121/1.1349185
|View full text |Cite
|
Sign up to set email alerts
|

Elevation localization and head-related transfer function analysis at low frequencies

Abstract: Monaural spectral features due to pinna diffraction are the primary cues for elevation. Because these features appear above 3 kHz where the wavelength becomes comparable to pinna size, it is generally believed that accurate elevation estimation requires wideband sources. However, psychoacoustic tests show that subjects can estimate elevation for low-frequency sources. In the experiments reported, random noise bursts low-pass filtered to 3 kHz were processed with individualized head-related transfer functions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
130
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(148 citation statements)
references
References 24 publications
12
130
1
5
Order By: Relevance
“…The auditory spatial cues involved in sound localization include interaural time (and/or phase) and intensity differences (ITDs and IIDs, respectively) in azimuth and pinna/headgenerated spectral cues in elevation that also assist front-back discrimination (Algazi et al 2001;Asano et al 1990;Middlebrooks 1992;Musicant and Butler 1984;Oldfield and Parker 1984b;Rayleigh 1907;Wightman and Kistler 1989b). For pure tones, ITDs are accompanied by interaural phase differences (IPDs) that are reliable only up to ϳ1.5 kHz in humans due to phase ambiguity coupled with declining neuronal temporal coding (phase-locking) at higher frequencies (Dreyer and Delgutte 2006;Johnson 1980;Joris and Yin 1992;Klumpp and Eady 1956;Zwislocki and Feldman 1956).…”
mentioning
confidence: 99%
“…The auditory spatial cues involved in sound localization include interaural time (and/or phase) and intensity differences (ITDs and IIDs, respectively) in azimuth and pinna/headgenerated spectral cues in elevation that also assist front-back discrimination (Algazi et al 2001;Asano et al 1990;Middlebrooks 1992;Musicant and Butler 1984;Oldfield and Parker 1984b;Rayleigh 1907;Wightman and Kistler 1989b). For pure tones, ITDs are accompanied by interaural phase differences (IPDs) that are reliable only up to ϳ1.5 kHz in humans due to phase ambiguity coupled with declining neuronal temporal coding (phase-locking) at higher frequencies (Dreyer and Delgutte 2006;Johnson 1980;Joris and Yin 1992;Klumpp and Eady 1956;Zwislocki and Feldman 1956).…”
mentioning
confidence: 99%
“…On the other hand, the role of low frequencies in vertical localization has also been reported by Morimoto et al [7]. Gardner [8] and Algazi et al [9] showed that torso reflections produce spectral notches in the HRTF below 3 kHz, which are additional localization cues for an elevated source.…”
Section: Introductionmentioning
confidence: 53%
“…0, for a sound source in the median plane, a torso reflection produces a spectral notch in the HRTF below 3 kHz when it is combined with the direct sound at the ear [8,9]. Algazi et al [9] showed that such a notch varies in frequency as a function of torso reflection delay, which is elevation-dependent. The torso reflection delay tends to increase as the elevation angle increases, and reaches its maximum when the source is in the "above" region.…”
Section: A New Hypothesis On the Role Of Acoustic Crosstalk And Torsomentioning
confidence: 99%
See 1 more Smart Citation
“…However humans are still able to localize sound in the median plane by what is known as monaural cues, which are related to the spectral changes introduced by the outer ears (i.e. pinnae) at high frequencies and other body structures like the torso at low frequencies [111]. Some studies have shown that these cues help listeners with complete hearing loss in one ear to localize the azimuth direction of a source with relatively high accuracy.…”
Section: Spectral Cuesmentioning
confidence: 99%